2023
DOI: 10.1186/s12871-023-02178-x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption may be associated with postoperative delirium in the elderly: the PNDABLE study

Xiaoyue Wu,
Ning Zhang,
Bin Zhou
et al.

Abstract: Objectives This study aimed to reveal the relationship between alcohol consumption and Postoperative delirium (POD) in the elderly. Methods We selected 252 patients from the Perioperative Neurocognitive Disorder And Biomarker Lifestyle (PNDABLE ) study. Patients in the PNDABLE database have been measured for Alzheimer-related biomarkers in CSF (Aβ40, Aβ42, P-tau, and tau protein). Mini-Mental State Examination (MMSE) was used to assess the preoper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…The research in this paper has increased the role of PA in reducing the incidence of POD. In order to further investigate the relationship between PA and POD, we added some confounding factors, the results show that Aβ42 plays a protective role in the occurrence of POD, while T-tau and P-tau play dangerous roles, and it corroborates the results of our group’s previous research ( Wu et al, 2023b ). The results were further validated in the groups of patients with MMSE > 28, diabetes, and coronary heart disease.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The research in this paper has increased the role of PA in reducing the incidence of POD. In order to further investigate the relationship between PA and POD, we added some confounding factors, the results show that Aβ42 plays a protective role in the occurrence of POD, while T-tau and P-tau play dangerous roles, and it corroborates the results of our group’s previous research ( Wu et al, 2023b ). The results were further validated in the groups of patients with MMSE > 28, diabetes, and coronary heart disease.…”
Section: Discussionsupporting
confidence: 83%
“…Obviously, a large number of studies have been reported on biomarkers and POD at present, but there is no effective measure to intervene in the increase or decrease of CSF biomarkers to improve the occurrence of POD. However, previous research in our group has found that the occurrence of POD may be reduced after adjusting lifestyle habits such as tea drinking and drinking (Lin et al, 2022;Wu et al, 2023b). As a well-known healthy lifestyle habit, it is reasonable to speculate that PA may be related to the occurrence of POD.…”
Section: Discussionmentioning
confidence: 78%
“…Alcohol consumption is another nutritional factor that has been shown to be associated with postoperative delirium. A study of 252 patients found alcohol to be a risk factor for POD, particularly in quantities larger than 24 grams per day on average (Wu et al, 2023). Additionally, excessive alcohol intake can interfere with nutrient absorption and metabolism, affect dietary choices, and impair liver function, all of which may exacerbate malnourishment and increase risk for POD (Butts et al, 2023).…”
Section: Association Of Malnutrition and Postoperative Deliriummentioning
confidence: 99%